Análise por superfícies de resposta do desempenho energético e emissões de um motor gerador dual com biodiesel e biogás enriquecido com hidrogênio. - Simon, Danilo (2025)
This study analyzes the dual-mode operation of compression ignition engines using biodiesel and biogas enriched with hydrogen as fuels, with the aim of enhancing energy efficiency and reducing emissions. Experimental results indicated that the partial replacement of diesel with the gaseous fuel yielded significant reductions in specific fuel consumption, reaching maximum values 21% compared to the exclusive use of diesel. The incorporation of hydrogen (12.5% of the total flow) into the biogas resulted in an average efficiency increase of 0.76%, compensating for the biogas's low calorific value and reduced volumetric efficiency, while variations in biodiesel concentration exhibited a non-linear effect, with average efficiency increments of 0.4%. Regarding emissions, an average reduction of 66.4% in carbon monoxide levels was observed with increasing load, along with an additional decrease of approximately 5% in CO emissions upon the addition of hydrogen. However, the dual-mode operation produced higher unburned hydrocarbon emissions compared to pure diesel, although hydrogen enrichment mitigated this effect by reducing them by 4.1%. Nitrogen oxide (NOₓ) emissions increased on average by 26.6% with hydrogen addition, but the dual-mode operation reduced these pollutants by 11.5% (enriched mode) and 33.3% (biogas exclusive mode) relative to pure diesel. Finally, the response surface methodology proved to be robust and reliable, as evidenced by experimental validation showing errors between 0.55% and 8.66% and a total uncertainty of 4.84%, thereby ensuring data reliability and reinforcing the potential of dual-mode operation to optimize compression ignition engines performance and mitigate emissions.